2015
DOI: 10.1163/15685381-00003010
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism of tropical green pit viper Trimeresurus (Cryptelytrops) macrops in Northeast Thailand

Abstract: Total body size for arboreal vipers is normally biased toward small males and larger females. We evaluated sexual dimorphism in adult and sub-adultTrimeresurus macrops, a small, arboreal green pit viper commonly found in Southeast Asia, but severely understudied. We evaluated morphological characters of 139 adultT. macropsobtained by active and opportunistic searches at Sakaerat Biosphere Reserve in northeast Thailand, from May 2012 to October 2014. We compared 7 external characters including residual index (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Research permissions for this separate project did not allow for direct disturbance of animals or their habitats, thus, we were not able to capture big‐eyed pit vipers for morphometric measurements (mass, length, fecundity). Sex was determined through external characteristics, primarily presence (male) or absence (female) of a white postocular stripe, which has been observed for this species at the site by Strine et al (2015). The primary author visually estimated big‐eyed pit viper size; if big‐eyed pit vipers appeared longer than 400 mm they were classified as adults (derived from Strine et al [2015], who observed sexual maturity for the smallest T. macrops in their study to be at 450 mm), if smaller they were classified as juveniles; no exact size was estimated, however.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research permissions for this separate project did not allow for direct disturbance of animals or their habitats, thus, we were not able to capture big‐eyed pit vipers for morphometric measurements (mass, length, fecundity). Sex was determined through external characteristics, primarily presence (male) or absence (female) of a white postocular stripe, which has been observed for this species at the site by Strine et al (2015). The primary author visually estimated big‐eyed pit viper size; if big‐eyed pit vipers appeared longer than 400 mm they were classified as adults (derived from Strine et al [2015], who observed sexual maturity for the smallest T. macrops in their study to be at 450 mm), if smaller they were classified as juveniles; no exact size was estimated, however.…”
Section: Methodsmentioning
confidence: 99%
“…Sex was determined through external characteristics, primarily presence (male) or absence (female) of a white postocular stripe, which has been observed for this species at the site by Strine et al (2015). The primary author visually estimated big‐eyed pit viper size; if big‐eyed pit vipers appeared longer than 400 mm they were classified as adults (derived from Strine et al [2015], who observed sexual maturity for the smallest T. macrops in their study to be at 450 mm), if smaller they were classified as juveniles; no exact size was estimated, however. All 3 female T. macrops observed in 2020 were found at the Sakaerat Environmental Research Station, which is within the core zone of the biosphere reserve (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The males may use it to locate females (Coupe, 2002), or it may be used as a tag, indicating areas where food is abundant (Clark, 2007). Social behavior has also been observed in captive indian pythons (Python morulus) and wild big-eyed pitvipers (Trimeresurus macrops), but nothing is known about frequency of such behavior in these species in the wild (Barker et al, 1979;Barnes et al, 2019).…”
Section: Social Behaviormentioning
confidence: 99%